An investigation into the relationship between anaerobic work capacity, percentage body fat and the grade of asthma in asthmatics and a healthy control group - M. Burger; M. Geyer; W. Regel; G. M. Smit; E. Terblanche; J. A. Hendry (AOSIS, 1991)
The goal of this study was to compare the anaerobic working capacity of asthmatic children to that of a healthy control group and to ascertain the relationship between the degree of asthma, anaerobic exercise and percentage body fat. A total of 41 children, 21 asthmatics and 20 healthy children (13-18 years) were tested. Three variables - percentage body fat, pulmonary function and fitness - were measured. It was found that there is very little difference between the asthmatic and the healthy child, with regard to anthropometric measurements, fitness and anaerobic working capacity. A poor correlation was found between percentage body fat, pulmonary function and anaerobic working capacity. The results further showed that there is a slight correlation between the percentage body fat and anaerobic working capacity. This tendency can only be confirmed with a larger random sample of children. The researchers conclude that asthmatics, irrespective of the degree of asthma, are not restricted as far as anaerobic activities are concerned. They can  therefore lead a normal healthy life and, as far as anaerobic exercise is  concerned, can compete on equal terms with healthy children.